Investigating the effects of high temperature on the performance of structural steel connections using FE analysis - Mohammed Al-Fakih, Kamal Ahmed (2019)
This thesis presents a numerical investigation on the effects of elevated temperature on the performance of structural steel connections using FE analysis. One of the factors that lead to the failure, and then to the collapse of the steel structure, is the high extreme temperature that undermines the integrity of the building. Consequently, it is necessary to take into consideration the introduction of fire safety measures in the design of buildings during the designing process. To evaluate the resistance of the steel structure to the fire, it is important to understand the effects and response of the elevated temperatures, to ensure the safety of steel structure at exposure to fire. Analysis of nonlinear connections is a complex science and there is no immediate and rapid solution to the problem. All the results of the accounts of the design connections cannot be verified only through the lab tests on a large scale. This leads to the loss of a great deal of time, effort and money. At present, with the availability of engineering simulation software. It is possible to overcome these problems. The aim of this study is to provide moment-rotation characteristics and corresponding parameters of the steel beam-to-column connection exposed to the elevated temperature. To achieve the objective, a simulation was carried out to study the effect of the elevated temperature on the angles connection between beam and column using the finite element analysis (FEA). Four types of connections; double-web angles (DWA), top and seat angles (TSA), end-plate (EP), and top and seat with double-web angles connections (TSA-DWA) were considered in this study. Eight different models of various cross sections under the effect of different loading and boundary conditions were examined. Materials non-linearity was modelled with the elastic-plastic definition properties including frictional contact between surfaces to simulate actual conditions. This research investigates the behaviour of steel at an elevated temperature from 25 °C to 700 °C. The analysis of results was compared with the experimental data available from the literature. The model behaviour validation shows that the model is in good agreement with the existing experimental results. The validated FE model was used to conduct further studies with new three-dimensional (3D) loading conditions in order to produce moment-rotation curve and enhance the understanding of steel joints behaviour on fire. In addition, the results showed for that the moment-rotation curve for all connections, the moment is decreased with increasing temperatures and in contrast, the rotation increased. Moreover, the loss of total capacity of connections is 18 % at 200 °C and increased to 58 % at 400 °C. For 600 °C, it reached 85 % and completely collapsed at temperatures higher than 700 °C. In addition, it is found that the deformation capacity is controlled by the possibility of fracture in the angle connection, in the failure of the bolts and thickness of angles. Therefore, factors such as bolts diameter, type of bolts, angles thickness and properties of materials can improve the connections behaviour.